2014
DOI: 10.1117/1.jbo.19.6.065004
|View full text |Cite
|
Sign up to set email alerts
|

Is the red fluorescence of dental plaque related to its cariogenicity?

Abstract: Abstract. It has been speculated that the red fluorescence emitted by dental plaque could be related to its cariogenicity. To test this hypothesis, we designed this crossover in situ study, with two experimental phases of 14 days each. Seventeen volunteers, wearing a palatal appliance with bovine enamel blocks, were instructed to drip a 20% sucrose solution (experimental group) or purified water (control group) onto the enamel blocks eight times daily. The specimens were removed after 4, 7, 10, and 14 days, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…Similar to other previous studies, 11,12,15 we observed that the R/ G fluorescence ratio was related to biofilm maturation, although the value did not change after six days. In addition, the R/G ratio was strongly correlated with green value rather than red value.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar to other previous studies, 11,12,15 we observed that the R/ G fluorescence ratio was related to biofilm maturation, although the value did not change after six days. In addition, the R/G ratio was strongly correlated with green value rather than red value.…”
Section: Discussionsupporting
confidence: 80%
“…[8][9][10][11] Although some researchers have demonstrated that the red fluorescence emitted by dental plaque is not an essential factor in cariogenicity, red fluorescence of biofilm indicates that these biofilms were mature. 12,13 When we observed plaque with QLF, it has been found that biofilms emitting red fluorescence were primarily composed of anaerobic bacteria that are related not only to caries but also to periodontitis. 13 Moreover, some studies have suggested that increases in red fluorescence according to the maturation of the biofilm are due to ecological changes in the biofilm and not increases in specific species.…”
Section: Introductionmentioning
confidence: 99%
“…1 Research is currently being undertaken to correlate plaque fluorescence with the progression of oral diseases, such as dental caries. [2][3][4][5] The three possible mechanisms by which changes in antecedent growth conditions and the local physicochemical environment (i.e., pH) could affect plaque's fluorescent emissions are as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an objective method could be less influenced by examiner's experience than would visual inspection. 4 Considering that LFpen and QLF (red fluorescence measurement) are methods based on the fluorescence emitted by microorganisms present in the caries lesions, 9,11,15 and since active caries lesions are more infected than inactive ones, 16 this possibility would be plausible. The old version of the LF method used with different drying times had been tested for this purpose previously, 28 but this methodology was not compared with visual inspection.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Thus, assessment of red fluorescence could be an adjunctive method for caries activity assessment, since active lesions are more infected than inactive ones. 16,17 To the best of our knowledge, however, no previous study was carried out to evaluate the accuracy of QLF in detecting occlusal caries lesions, nor for the assessment of caries activity status in primary teeth.…”
Section: Introductionmentioning
confidence: 99%